2017
DOI: 10.1186/s12870-016-0960-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative RNA-seq based transcriptomic analysis of bud dormancy in grape

Abstract: BackgroundBud dormancy is an important biological phenomenon of perennial plants that enables them to survive under harsh environmental circumstances. Grape (Vitis vinifera) is one of the most grown fruit crop worldwide; however, underlying mechanisms involved in grape bud dormancy are not yet clear. This work was aimed to explore the underlying molecular mechanism regulating bud dormancy in grape.ResultsWe have performed transcriptome and differential transcript expression analyses of “Shine Muscat” grape bud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 48 publications
4
63
0
Order By: Relevance
“…Significantly enriched gene ontology (GO) terms in clusters 1, 2, 4, and 7 constructed by cluster analysis (Fig. 3) changes, such as dormancy release , Khalil-Ur-Rehman et al, 2017, Liu et al, 2012, cold hardening or both (John et al, 2016).…”
Section: Levels In Terminal Flower Budsmentioning
confidence: 99%
“…Significantly enriched gene ontology (GO) terms in clusters 1, 2, 4, and 7 constructed by cluster analysis (Fig. 3) changes, such as dormancy release , Khalil-Ur-Rehman et al, 2017, Liu et al, 2012, cold hardening or both (John et al, 2016).…”
Section: Levels In Terminal Flower Budsmentioning
confidence: 99%
“…Insufficient cold accumulation during this period generally results in non-uniform flowering and reduced fruit set. The grape buds in southeast China can achieve their chilling requirement at the end of February and bloom in the following spring ( Khalil-Ur-Rehman et al, 2017 ). Therefore, to allow coordinated and early production of economically viable yields, artificial substitutes are required for chilling to avoid prolonged dormancy in these regions ( Zheng et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of gibberellin, the stable GID1-GA-DELLA complex is recognized by the SCF SLY1 complex which ubiquintylates the DELLA proteins and causes their degradation by the 26S proteasome [71,72]. It has been reported previously that GID1-transcripts are upregulated during bud dormancy in grapevine while transcripts of DELLA are downregulated [73]. Similarly, we found that the GID1B receptor transcript is upregulated during bud dormancy while the DELLA-protein SLR1-like (SLENDER RICE 1 LIKE) are downregulated.…”
Section: Discussionmentioning
confidence: 99%